Challenges and Priorities in the Management of HIV/HBV and HIV/HCV Coinfection in Resource-Limited Settings - Easterbrook, Philippa; Sands, Anita; Harmanci, Hande (Seminars in Liver Disease, 2012)
Liver disease due to chronic hepatitis B virus (HBV) and hepatitis C virus (HCV) infection is now emerging as an increasing cause of morbidity and mortality in human immunodeficiency virus- (HIV-) infected persons in resource-limited settings (RLS). Existing management guidelines have generally focused on care in tertiary level facilities in developed countries. Less than half of low-income countries have guidance, and in those that do, there are important omissions or disparities in recommendations. There are multiple challenges to delivery of effective hepatitis care in RLS, but the most important remains the limited access to antiviral drugs and diagnostic tests. In 2010, the World Health Assembly adopted a resolution calling for a comprehensive approach for the prevention, control, and management of viral hepatitis. We describe activities at the World Health Organization (WHO) in three key areas: the establishment of a global hepatitis Program and interim strategy; steps toward the development of global guidance on management of coinfection for RLS; and the WHO prequalification program of HBV and HCV diagnostic assays. We highlight key research gaps and the importance of applying the lessons learned from the public health scale-up of ART to hepatitis care.
Keywords: HIV-hepatitis B coinfection; HIV-hepatitis C coinfection; resource-limited settings